Sexual homicide: does anything matter beyond sexual sadism? - DeLisi, Matt (Routledge handbook of homicide studies, 2024)
Sexual homicide is among the rarest, most extreme forms of antisocial behavior. Several studies suggest that paraphilic disorders or conditions especially sexual sadism are a major correlate of sexual homicide. Unfortunately, many studies infer sexual sadism from crime scene indicators, not diagnostic history. Drawing on a large sample of individuals convicted of aggravated murders and sentenced to death in the United States, the current study examined the association of lifetime sexual sadism diagnosis and nine criminal career, demographic, and forensic covariates on sexual homicide offending and necrophilic sexual homicide offending. Net the effects of these variables, sexual sadism increased the odds of sexual homicide by 2,055% and increased the odds of necrophilic sexual homicide by 828%. With one exception, sexual sadism rendered the effects of other study variables nonsignificant once it was specified in the models. Implications for theory and research are provided.